Protein Interactions Investigated by the Raman Spectroscopy for Biosensor Applications. (24th April 2012) - Kengne-Momo, R. P.; Daniel, Ph.; Lagarde, F.; Jeyachandran, Y. L.; Pilard, J. F.; Durand-Thouand, M. J.; Thouand, G.
Abstract : Interaction and surface binding characteristics of staphylococcal protein A (SpA) and an anti- Escherichia coli immunoglobulin G (IgG) were studied using the Raman spectroscopy. The tyrosine amino acid residues present in the α -helix structure of SpA were found to be involved in interaction with IgG. In bulk interaction condition the native structure of proteins was almost preserved where interaction-related changes were observed in the overall secondary structure ( α -helix) of SpA. In the adsorbed state, the protein structure was largely modified, which allowed the identification of tyrosine amino acids involved in SpA and IgG interaction. This study constitutes a direct Raman spectroscopic investigation of SpA and IgG (receptor-antibody) interaction mechanism in the goal of a future biosensor application for detection of pathogenic microorganisms.